Erratum to “Development and Validation of the Islamic Work Exemplary Scale in Indonesia” [Islamic Guidance and Counseling Journal 6(2) 2023] - Sumin Sumin; Heri Retnawati; Wajidi Sayadi (Islamic Guidance and Counseling Journal, 2023)
Refers to:Sumin, S., Retnawati, H., & Sayadi, W. (2023). Development and Validation of the Islamic Work Exemplary Scale in Indonesia. Islamic Guidance and Counseling Journal, 6(2). https://doi.org/10.25217/0020236392000Erratum:The authors requested a revision to the abstract in the original publication of this article. Specifically, at the behest of the corresponding author, the phrase "test validity and reliability" was amended to "Validity and Reliability checking". Subsequently, this correction has been implemented in the original article.